Antimicrobial multidrug resistance of Escherichia coli from broiler farms in Zhanjiang, China - CuiYi Liao; JinJu Peng; Shuaishuai Luo; Xingpeng Xie; Yang Li; Haotian Ma; Mengbo Yu; Yuexia Ding; Yi Ma (PLoS ONE, 2025)
Guangdong Province is an important area of poultry breeding in China. Zhanjiang city is located in the western part of Guangdong Province, where there are many broiler farms. To investigate antimicrobial resistance (AMR) and the presence of resistance genes in Escherichia coli from broiler farms, a total of 220 samples were collected from soil and feces at eight broiler farms. Subsequently, 220 strains of E. coli were isolated for drug resistance analysis and detection of AMR genes. The results revealed that the isolated E. coli strains exhibited high prevalence of multidrug resistance to 12 antimicrobial drugs including amoxicillin, tetracycline, cotrimoxazole and sulfisoxazole. Among the isolated strains, 95% of the isolates were resistant to more than three antimicrobial agents; notably, thirty-nine strains showed multidrug resistance to ten tested drugs, while four strain exhibits multidrug resistance to as many as fifteen antibacterial drugs. Additionally, seven AMR genes such as bla TEM and sul2 were detected in over half (≥50%) of the isolated E. coli samples; thirteen AMR genes had relatively low detection prevalence (≤30%). Correlation analysis indicated a strong association between certain AMR genes ( bla TEM , pexA, aadA1, bla AIM , ant(3")-I, sul2, sul3, tet(D) ) and AMR (≥50%). In conclusion, E.coli strains obtained from soil and fecal samples in broiler farms exhibited multidrug resistant phenotypes along with carrying various AMR genes. This provides a reference for the scientific control of E. coli multidrug resistance in this area.